Team Teaching and Team Learning in the Language Classroom Collaboration for innovation in ELT - Tajino, Akira; Stewart, Tim; Dalsky, David (Routledge Research in Language Education, 2016)
This book reignites discussion on the importance of collaboration and innovation in language education. The pivotal difference highlighted in this volume is the concept of team learning through collaborative relationships such as team teaching. It explores ways in which team learning happens in ELT environments and what emerges from these explorations is a more robust concept of team learning in language education. Coupled with this deeper understanding, the value of participant research is emphasised by defining the notion of 'team' to include all participants in the educational experience. Authors in this volume position practice ahead of theory as they struggle to make sense of the complex phenomena of language teaching and learning. The focus of this book is on the nexus between ELT theory and practice as viewed through the lens of collaboration. The volume aims to add to the current knowledge base in order to bridge the theory-practice gap regarding collaboration for innovation in language classrooms.